Behavioral Governance and Self-Conscious Emotions: Unveiling Governance Implications of Authentic and Hubristic Pride - Bodolica, Virginia 1976-; Spraggon, Martin (2011)
The main purpose of this article is to elucidate the bright connotation of the self-conscious emotion of pride, namely authentic pride, in the broader context of behavioral governance literature. Scholars in the field of psychology suggest that authentic and hubristic pride represent two facets of the same emotional construct. Yet, our review indicates that in the extant governance research pride has been treated as an exclusively dark leadership trait or self-attribution bias, thereby placing hubris among the main causes of managerial failure. After conceptually differentiating the two aspects of pride, we identify and discuss the myriad of positive governance implications stemming from firm members’ tendency toward authentic pride. We argue that the examination of both positive and negative facets of pride constitutes a critical complement to the existing governance landscape largely dominated by economic theories and formal mechanisms of control. This article allows practitioners to better understand the emotional processes involved in governance that are needed to predict the workplace effectiveness of employees, identify individuals prone to experience authentic pride in the early stages of the recruitment process, and design specific interventions for acting upon and putting emotional energy into productive use.
Keywords: decision makers; hubristic pride; Authentic pride; behavioral governance; self-conscious emotions